2020
DOI: 10.3390/ijerph17155512
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Mitragynine Content, Levels of Toxic Metals and the Presence of Microbes in Kratom Products Purchased in the Western Suburbs of Chicago

Abstract: Kratom (Mitragyna speciosa, Korth) is a tree-like plant that is indigenous to Southeast Asia. Kratom leaf products have been used in traditional folk medicine for their unique combination of stimulant and opioid-like effects. Kratom is being increasingly used in the West for its reputed benefits in the treatment of pain, depression and opioid use disorder. Recently, the United States Food and Drug Administration and Centers for Disease Control have raised concerns regarding the contamination of some kratom pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…has been recognized in the literature, but thorough testing for Salmonella in our patient was negative. 10 The syndrome of drug-induced colitis has well described; histopathological findings of drug-induced colitis are nonspecific and can be similar to ischemic colitis, which may present a diagnostic dilemma. 11 To the best of our knowledge, this is only the second reported patient to require orthotopic liver transplantation for acute liver failure as a consequence of kratom ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…has been recognized in the literature, but thorough testing for Salmonella in our patient was negative. 10 The syndrome of drug-induced colitis has well described; histopathological findings of drug-induced colitis are nonspecific and can be similar to ischemic colitis, which may present a diagnostic dilemma. 11 To the best of our knowledge, this is only the second reported patient to require orthotopic liver transplantation for acute liver failure as a consequence of kratom ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy suggests that the problem might not be related to the toxicity of kratom per se, but rather the poor quality of some kratom products being sold in the West, including the United States. Various studies indicate that many kratom products may be adulterated with other drugs or be contaminated with toxic metals and infectious microbes (Prozialeck et al, 2019;Prozialeck et al, 2020). In addition to the potential for acute toxicity, kratom can produce a state of physical dependence for which the term "kratom use disorder" has been coined.…”
Section: Kratom Safety Concernsmentioning
confidence: 99%
“…An established quantitative liquid chromatography mass spectrometry method was conducted (62) and found that the sample obtained from the patient is kratom due to the presence of mitragynine (102 mg/g kratom powder) and 7-hydroxymitragynine (0.8 mg/g kratom powder). The extracted kratom sample was analyzed for the presence of 13 opioids and 8 benzodiazepines by comparing the chromatograms to those of the reference mixtures Pain Management Multicomponent Opiate Mixture-13 solution and Benzodiazepine Multi-component Mixture-8 solution.…”
Section: Kratom Sample Analysismentioning
confidence: 99%